Dietary supplementation effects of the levels of Neem (Azadirachta indica) leaf extracts as phytogenic feed additive on the growth performance in broiler chicks (Asian Journal of Medical and Biological Research, 2021)
The effects that Neem leaf extract on overall growth, feed conversion ratio (FCR), dressed weight and organs weight of broiler chickens to justify its inclusion in the diet of growing broiler chickens. 120 day old chicks divided into four treatment groups T1, T2, T3 and T4 of thirty (30) birds each were administered clean drinking water with 3gm, 4gm, 5gm and 0g neem extract respectively. Impacts of neem extract treatments on growth indices suggested that Neem extract favored growth with final body weight range of 1709gm and 1763gm. Organ weights showed no deviation from standard values for healthy broiler birds. Highest growth was observed in group T3 (1763.6±141.37gm) followed by T1, T2 and lowest was in T4 group (1565.4±161.25gm). Birds on 5gm of Neem extract in their drinking water out performed birds in other treatments in assessed growth rate indices. We therefore conclude that 5gm of Neem extract in their drinking water growing broiler birds encourages healthy growth and may serve as supplements for antibiotics, especially when birds are raised in areas with minimal access to veterinary service.Asian J. Med. Biol. Res. March 2021, 7(1): 64-68